2015
DOI: 10.2298/pif1503169z
|View full text |Cite
|
Sign up to set email alerts
|

In vitro and in vivo effects of Pseudomonas spp. and Bacillus sp. on Fusarium acuminatum, Botrytis cinerea and Aspergillus niger infecting Cucumber

Abstract: SummaryCucumber (Cucumis sativus L) is an important member of the Cucurbitaceae family. Production of healthy nursery is necessary for high-quality production of this crop in greenhouses and in fields. With the idea of minimizing the use of pesticides and mineral fertilizers to preserve soil quality, we investigated the effects of plant growth promoting bacteria (PGPB) on growth promotion and protection of cucumber plants from phytopathogenic fungi. The effects of Pseudomonas spp. strains with different antifu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 26 publications
1
4
0
Order By: Relevance
“…The increase in N, P and K content in Ocimum basilicum inoculated with PGPR Pseudomonas putida and Azotobacter chroococcum was previously reported (Ordookhani et al, 2011). In addition, as stated by the other authors (Zdravković et al, 2015), and as it was done in this study, it is suggested that bacterial suspension should be applied during the growth phase of plants when the treatment has the greatest impact, i.e. when enzyme activity is the strongest.…”
Section: Morphological and Chemical Growth Parameters Of Plantssupporting
confidence: 59%
See 1 more Smart Citation
“…The increase in N, P and K content in Ocimum basilicum inoculated with PGPR Pseudomonas putida and Azotobacter chroococcum was previously reported (Ordookhani et al, 2011). In addition, as stated by the other authors (Zdravković et al, 2015), and as it was done in this study, it is suggested that bacterial suspension should be applied during the growth phase of plants when the treatment has the greatest impact, i.e. when enzyme activity is the strongest.…”
Section: Morphological and Chemical Growth Parameters Of Plantssupporting
confidence: 59%
“…In this respect, different isolates of fluorescent Pseudomonas species take prominent place. Consequently, these isolates have been intensively studied (Couillerot et al, 2009;Ivanović et al, 2009;Jošić et al, 2012;Jošić et al, 2015;Zdravković et al, 2015;Mrkovački et al, 2016).…”
mentioning
confidence: 99%
“…These facts also support the idea that collected rhizobacteria had a stronger effect on B. cinerea compared to F. oxysporum coinciding with the study done in Saudi Arabia as mentioned earlier 41 . In another study by Zdravković et al 60 ., the effects of Pseudomonas spp. and Bacillus sp.…”
Section: Resultsmentioning
confidence: 91%
“…According to Podile and Kishore (2006), PGPR and their interactions with plants are exploited commercially and hold great promise for sustainable agriculture. Applications of these associations have been investigated in maize, wheat, oat, barley, peas, canola, soy, potatoes, tomatoes, lentils, radicchio and cucumber (Gray and Smith, 2005, Jošić et al 2012, Zdravković et al 2015.…”
Section: Discussionmentioning
confidence: 99%
“…strain Q10 through their effect on the main chemical growth parameters (content of N, P, K, Ca and Mg) and yield of dry biomass of radicchio aerial parts and root. Pseudomonas isolate was selected on the basis of previous studies that confirmed its intrinsic antibiotic resistance and plant growth promoting traits: phosphate solubilization, siderophore and indoleacetic acid production, enzymatic activity (Jošić et al 2012, Jošić et al 2012a, Zdravković et al 2015. In addition, Bacillus sp.…”
Section: Discussionmentioning
confidence: 99%